Analysis of surface intergrity and tool wear during machining high thermal conductivity steel 150 (HTCS- 150) - Wan Mohd Azahar Wan Mohd Yusoff (2018)
High Thermal Conductivity Steel 150 (HTCS-150) is a new material that applied as a die to assist efficient heat transfer in a hot stamping process. Machining process of HTCS- 150 die involved from roughing to finishing process assisted by CADCAM and CNC machining. This research concentrated on study when finish machining of HTCS-150 using ball nose end mill TiAlN coated carbide insert. The intent of this research is to develop the regression model and optimization focused on the relationship between the cutting parameters (cutting speed, feed rate and axial depth of cut) and the machining outcome (surface roughness and tool wear) using Response Surface Methodology (RSM) and Box-Behknen experimental design. Consequent to model development, Analysis of Variance (ANOVA), Scanning Electron Microscope (SEM) were employed to identify significant factors and surface characteristics that influenced the surface roughness and tool wear. Experimental processes were carried out using Variaxis MAZAK CNC 5 axis vertical Milling, assisted by the Design Expert 6.0 analysis software. Ranges of cutting parameters selected were 484-553 m/min cutting speeds, 0.31-0.36 mm/tooth feed rates, 0.1-0.5 mm axial depth of cut and 0.01 mm constant radial depth of cut. The results show the model develop adequately represent the process with modeling validation runs within the 90% of prediction interval and their residual errors compared to the predicted values were less than 10%. The optimization results sh9w that the lowest surface roughness achieved at 518.50 m/min cutting speed, 0.31 mm/tooth feed rate of and 0.10 mm axial depth of cut. Combination of cutting parameters for the lowest tool wear recorded as 551 m/min cutting speed, 0.36 mm/tooth feed rate and 0.18 mm axial depth of cut. The ANOVA analysis shows that for surface roughness, most influenced cutting parameters was cutting speed followed by axial depth of cut and feed rate. Meanwhile, for tool wear, feed rate recorded as most influenced cutting parameter followed by cutting speed and axial depth of cut. Observation using SEM observed that feed marks, material pullout, adhered material and surface porosity were major defects on the machined surface. For tool wear, coating delamination, abrasive wear, Built-up Layer, adhesive wear and chipping were among failure mechanisms observed. The analysis results from this research are useful to increase the surface quality and decrease the tool wear as the industry player can reduce the period for finishing process to get the finest quality surface and lowest production cost.